Analysis of the concrete-steel interface in specimens exposed to the weather and immersed in natural sea water - Sosa, M. R.; Pérez López, Tezozomoc; Moo-Yam, V. M. J.; Chávez, E.; Pérez-Quiroz, J. T. (Revista ALCONPAT, 2018)
The electrochemical behavior in reinforced concrete elements without and with additión of sodium chloride (NaCl) in the mixing water, in exposed in a marine/tropical environment was evaluated. The monitoring consisted in measuring corrosión potential (Ecorr), carbonatión front advance (xCO2) and photographic record of the concrete/steel interface at different stages of the exposure time period. In the outdoor exposure it was observed that the additión of NaCl in the mixing water favored the advancement of carbonatión, without showing the beginning of corrosión. The presence of chloride was determinant in the beginning and development of the process of corrosión, as much in exposure to the intemperie as in immersión.